1993
DOI: 10.1002/jnr.490340509
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C activity modulates myelin gene expression in enriched oligodendrocytes

Abstract: Protein kinase C (PKC) and its potential role in myelin gene expression were investigated in primary cultured rat oligodendrocytes. The major myelin genes were expressed in a developmentally coordinated manner in cultured oligodendrocytes. PKC activity in these cells was similarly regulated with differential expression of PKC isozyme mRNAs. PKC-gamma mRNA was expressed transiently and was most abundant in 9-day cells in vitro. PKC-alpha and PKC-beta mRNAs were present at low levels throughout development in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 83 publications
3
42
1
Order By: Relevance
“…PKCmediated posttranscriptional suppression of myelin gene expression is most profound in differentiating OLs at or before the onset of myelin protein synthesis (19). This correlates well with our data showing that MASS1 regulates MAG protein stability.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…PKCmediated posttranscriptional suppression of myelin gene expression is most profound in differentiating OLs at or before the onset of myelin protein synthesis (19). This correlates well with our data showing that MASS1 regulates MAG protein stability.…”
Section: Discussionsupporting
confidence: 91%
“…PKC was previously shown to play a role in regulating myelin proteins levels (19). To further reveal the mechanism and assess MASS1 regulation of PKC in vivo, we used primary OL cultures and found that phosphorylated PKCδ/θ levels were dramatically decreased in Frings OLs vs. control (Fig.…”
Section: Mass1 Is Expressed In Oligodendrocytesmentioning
confidence: 91%
“…Some embryos and fetuses were fixed in 4% paraformaldehyde, Histochoice (AMRESCO), or snap frozen in OCT and cryosectioned or embedded in paraffin and sectioned. Immunostaining was performed as described previously (35) by using monoclonal antibodies to glial fibrillary acidic protein (GFAP) (G-A-5; Sigma) and myelin phospholipid protein (PLP) (M2; ref. 35).…”
Section: Methodsmentioning
confidence: 99%
“…Immunostaining was performed as described previously (35) by using monoclonal antibodies to glial fibrillary acidic protein (GFAP) (G-A-5; Sigma) and myelin phospholipid protein (PLP) (M2; ref. 35).…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately the only antibody available to detect DM20 protein by Western blot analysis recognizes a Cterminal epitope, which is altered in Plp jp PLP/DM20 proteins. Thus, only the mutant PLP protein in Plp jp mice could be examined due to the existence of PLP-specific antibodies [21]. Although the amounts, if any, of mutant DM20 in Plp jp sciatic nerve could not be determined, the PCR data (Fig.…”
Section: Downregulation Of the Plp Gene And The Plp(+)z Transgene In mentioning
confidence: 99%